2023
DOI: 10.1007/s44197-023-00084-6
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Transplant Recipients Infected with Omicron BA.1 and BA.2: A Single-Center Retrospective Study in Saudi Arabia

Abstract: The outcome of transplant recipients is variable depending on the study population, vaccination status and COVID-19 variants. Our aim was to study the impact of Omicron subvariants on the mortality of transplant recipients. We reviewed the results of SARS-CoV-2 whole genome sequence of random isolates collected from 29 December 2021 until 17 May 2022 in King Faisal Specialist Hospital and Research center, Jeddah (KFSHRC-J), Saudi Arabia performed as hospital genomic surveillance program for COVID-19 variants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Mortality rates for hospitalized transplant recipients infected with omicron variants vary: 20% at a tertiary health center in Jeddah, Saudi Arabia ( 67 ), 4% in a US study ( 62 ), and 16% in Spain ( 65 ). Three doses of vaccine do not appear to reduce the mortality rate in transplant recipient patients ( 64 ), but early use of SARS-CoV-2 monoclonal antibodies (in addition to vaccination) is associated with preventing severe disease progression and oxygen demand ( 68 ).…”
Section: Clinical Characteristics and Prognosis Of Organ Transplant R...mentioning
confidence: 99%
See 1 more Smart Citation
“…Mortality rates for hospitalized transplant recipients infected with omicron variants vary: 20% at a tertiary health center in Jeddah, Saudi Arabia ( 67 ), 4% in a US study ( 62 ), and 16% in Spain ( 65 ). Three doses of vaccine do not appear to reduce the mortality rate in transplant recipient patients ( 64 ), but early use of SARS-CoV-2 monoclonal antibodies (in addition to vaccination) is associated with preventing severe disease progression and oxygen demand ( 68 ).…”
Section: Clinical Characteristics and Prognosis Of Organ Transplant R...mentioning
confidence: 99%
“…There are currently insufficient data showing that omicron variants produce a different spectrum of disease. Abeer et al ( 67 ) studied omicron patients (confirmed by whole genome sequencing) and did not find a specific omicron variant associated with poor prognosis. A recent study from South Africa showed that omicron B.A 1, 2, 4, and 5 were associated with decreased vaccine efficacy and an increase in hospitalization rates 4 months after booster vaccination.…”
Section: Clinical Characteristics and Prognosis Of Organ Transplant R...mentioning
confidence: 99%